The emotional labour of quality improvement work in end of life care: a qualitative study of Patient and Family Centred Care (PFCC) in England - Richard Boulton; Annette Boaz (BMC, 2019)
Abstract Background There is a growing emphasis on understanding patient experience in order to inform efforts to support improvement. This paper reports findings from an implementation study of an evidence-based intervention called Patient and Family Centred Care (PFCC) designed to tap into patient experiences as a basis for improvement. In this study the PFCC intervention was spread to a new service area (end of life care) and delivered at scale in England. The findings presented here focus specifically on one key aspect of the intervention: staff shadowing of patients, and the experiences of staff carrying out shadowing for the purposes of service improvements. Methods The study methods were ethnographic observations of key events, semi-structured interviews with members of participating teams and the programme implementation support team and managers, and a review of the documents used in the set up and running of the programme. Results One of the key strengths of the PFCC approach is to encourage staff through shadowing to engage with patient experience of services. Many staff described the process of shadowing as a transformative experience that alerted them to immediate areas where their services could be improved. However, engaging with patient experience of end of life care services also had unintended consequences for some staff in the form of emotional labour. Furthermore, we observed difficulties encountered by staff that are not accounted for in the existing PFCC literature relating to how care service structures may unevenly distribute the amount of 'emotional labour' that staff members need to invest in implementing the programme. Conclusions Connecting with patient experience is a crucial aspect of a number of quality improvement interventions that aim to help staff to engage with the lived experience of their services and reconnect their motivations for working in the health care system. However, there may be unintended consequences for health care service staff, particularly in sensitive areas of service delivery such as end of life care. The 'emotional labour' for staff of engaging in quality improvement work informed by patient experience should be considered in planning and supporting patient experience led quality improvement.